Pojęcia niezależności w algebrach z działaniami co najwyżej dwuargumentowymi - Chwastyk, Anna
In 1966 E. Marczewski introduced a general notion of independence, which contained as special cases the majority of independence notions used in various branches of mathematics - independence with respect to a family Q of mappings in an abstract algebra (Q-independence).
Keywords: Q-niezależność; algebra Stone'a; retrakcja